Comminuted navicular fracture treated with an internal fixation plate – Technical Tip - Mansur, Henrique; de Lucena da Silva, Landweherle; Maranho, Daniel Augusto (Journal of the Foot & Ankle, 2022)
Fractures of the navicular are relatively uncommon lesions. Comminuted fractures of the navicular body may be associated with focal bone collapse and loss of integrity of the medial column of the midfoot with gross instability, leading to deformities and potential early osteoarthritis. The treatment is challenging due to the difficulties to maintain the length and stability of the midfoot medial column and restoring the anatomy without damaging the vascular supply. Here we present an option for the surgical treatment of comminuted fractures of the navicular using a low-profile locking plate with the “bridge” principle as a temporary internal fixator. The technique consists of restoring the navicular anatomy by fixing the larger fragments with screws and applying indirect reduction of minor fragments. The bone length is maintained by a bridge-plating system with screws inserted into the talus and the medial cuneiform, crossing the talonavicular and naviculocuneiform joints. Implants are removed after fracture healing. Level of Evidence: V; Therapeutic Study; Expert Opinion.